Beyond phosphorus: synthesis, reactivity, coordination behaviour and catalytic properties of 1,1'-bis(diphenylstibino)ferrocene - Schulz, Jiří; Antala, Jakub; Císařová, Ivana; Štěpnička, Petr (Dalton transactions (Cambridge, England, 2023)
Compared to their widely studied phosphine counterparts, ferrocene stibines have received only marginal attention thus far. This paper describes the synthesis of 1,1'-bis(diphenylstibino)ferrocene (1*), which is an antimony analogue of the ubiquitous dppf, and our investigations into the reactivity and coordination behaviour of this compound. Thus, distibine 1 was oxidised to stiboranes fc(SbPh2X2)2 (X = Cl, 2*; F, 6*; fc = ferrocene-1,1'-diyl) and to stibine-stiborane Ph2SbfcSbPh2F2 (5*). Compounds 2 and 6 were easily hydrolysed to produce ferrocenophanes fc[SbPh2XOSbPh2X] (X = Cl, 3*; F, 7*). Removing the halogen from 3 with silver(I) salts afforded the corresponding ferrocenophanes with O-bound oxyanions, fc[SbPh2ZOSbPh2Z] (Z = NO3, 4a*; ClO4, 4b*), which were alternatively prepared from 2 and also converted back to 2 by adding a chloride source. Through investigations into the coordination behaviour of distibine 1, the following compounds were isolated and characterised: [(μ-ClO4)2{Ag(1-κ2Sb,Sb')}2] (8*), [Ag(1-κ2Sb,Sb')2]X (X = ClO4, 9a; SbF6, 9b*), [(μ(Sb,Sb')-1){(arene)MCl2}2] (10*, 11*) and [(arene)MCl(1-κ2Sb,Sb')][PF6] (12*, 13*; 10, 12: M/arene = Ru/η6-p-cymene, 11, 13; Rh/η5-C5Me5), [(η5-C5Me5)RuCl(1-κ2Sb,Sb')] (14), [MCl2(1-κ2Sb,Sb')] (M = Pd, 15*; Pt, 16*), [Pd(1-κ2Sb,Sb')2]X2 (X = BF4, 17a; SbF6, 17b*), [Pd(η2-ma)(1-κ2Sb,Sb')] (18*; ma = maleic anhydride), [(μ(Sb,Sb')-1)(AuCl)2] (19*), and [Au(1-κ2Sb,Sb')2]X (X = AuCl2, 20a*; SbF6, 20b*). Inspection of the structural parameters suggested that complexes featuring 1 exhibit less sterically strained structures than their dppf analogues due to longer M-Sb and Sb-C bonds, which reduce crowding around the ligated metal centre. Cyclic voltammetry and DFT calculations revealed that the primary electrochemical oxidation of 1 is reversible and occurs at the ferrocene unit. Based on preliminary catalytic tests in Suzuki-Miyaura biaryl coupling, Pd-1 complexes exhibited a lower efficiency than their respective Pd-dppf analogues. (An asterisk indicates that the crystal structure has been determined.).